2007
DOI: 10.1111/j.1365-2699.2006.01647.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of endemism and species richness patterns in the Australian Anura

Abstract: Aim  To assemble a continental‐scale data set of all available anuran records and investigate trends in endemism and species richness for the Anura. Location  Continental Australia. Methods  97,338 records were assembled, covering 75% of the continent. A neighbourhood analysis was applied to recorded locations for each species to measure richness and endemism for each half‐degree grid square (c. 50 km) in the continent. This analysis was performed for all anurans, and also for each of the three main anuran fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 26 publications
(73 reference statements)
1
90
0
2
Order By: Relevance
“…The Pilbara region is host to only 13 species of frogs, slightly more diverse than the surrounding arid regions which are not diverse relative to the northern tropics, eastern coast and south-west (Slatyer et al 2007;Tyler and Doughty 2009;Powney et al 2009). Below we briefl y review some broad patterns identifi able from distribution maps.…”
Section: Biogeographic Patterns In Frogs Of the Pilbaramentioning
confidence: 99%
“…The Pilbara region is host to only 13 species of frogs, slightly more diverse than the surrounding arid regions which are not diverse relative to the northern tropics, eastern coast and south-west (Slatyer et al 2007;Tyler and Doughty 2009;Powney et al 2009). Below we briefl y review some broad patterns identifi able from distribution maps.…”
Section: Biogeographic Patterns In Frogs Of the Pilbaramentioning
confidence: 99%
“…The Kimberley region of Western Australia (WA) is home to approximately 40 species of frogs, and is a region of pronounced endemism within the Australian frog fauna Slatyer et al 2007;Tyler and Doughty 2009;Bowman et al 2010;Powney et al 2010;Doughty 2011). Some species are common and widely distributed in northern Australia, such as Cyclorana australis, Litoria caerulea and Platyplectrum ornatum, with ranges often extending from the Kimberley region beyond Cambridge Gulf, through the Top End (northern Northern Territory [NT]) and in to Queensland.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we should delimit the distributions of endemic taxa ideally using natural and geographic boundaries rather than administrative boundaries. Moreover, two types of errors (i. e., the overweighting of the widespread species regarded in the literature but with few observational records; the erroneous records for species with narrow recorded ranges which create comparatively high endemism scores in wrong places), should be emphasized when the distributions of endemics are being interpreted (Slatyer et al, 2007). Despite these issues, exploring the patterns of endemism and the distributions of endemics is important for understanding regional characters, compositions and evolutionary process of fauna, and also is of particular interest in the development of integrative conservation strategies (Jablonski, 1986;Grau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous biogeographic studies on amphibians in China mainly focused on threatened species, diversity across all species, or elevational patterns of regional frogs (Fu et al, 2006;Xie et al, 2007;Jiang et al, 2010). It is suggested that the level of available survey efforts, the consequent number of records available for assessment, and the identification of new species can strongly influence biogeographic assessments (Slatyer et al, 2007). Molecular analyses are increasingly used in systematics and some species complexes or cryptic species are recognized (e. g., Nishikawa et al, 2011b;Yang et al, 2011).…”
Section: Endemic Amphibians and Their Distributions In Chinamentioning
confidence: 99%